ANALISIS JENIS BUDAYA ORGANISASI DAN KOMPETENSI MANAJERIAL DI PT XYZ - Yoga Putera Pratama; Lindawati Kartika (STIE DWI SAKTI BATURAJA, 2017)
PT XYZ as one of the general insurance companies must have an effective organisation performance to change. The purposes of this study are to analyze the type of realization and expected organization culture and to analyze employee perceptions of the managerial competence of PT XYZ. Data analysis using Organizational Culture Assessment Instrument, Management Skill Assessment Instrument (MSAI) and Improvement Performance Analysis (IPA). The results of the research showed that PT XYZ is dominated by the clan and hierarchy culture. While the expected type of culture in PT XYZ is clan and adhocracy culture. The state of managerial competence in PT XYZ is in the